Nurturing Mualaf Management and Introduction to Islam in London United Kingdom : A Case study in Islamic Cultural Centre London - Masruri Nursad; Masyitoh; Hilali Basya (Universitas Djuanda, 2026)
This research examines the role and management of the Islamic Cultural Centre (ICC) in London in promoting Islam and fostering converts in the United Kingdom, a context marked by the growing Muslim population driven by immigration, higher birth rates within Muslim communities, and an increasing number of native Britons embracing Islam. Employing a qualitative descriptive-analytical approach with a case study design, the study draws on data from observation, in-depth interviews, and document analysis. The findings indicate that ICC London implements a systematic and adaptive management model for convert development through structured Islamic education, spiritual mentoring, and continuous social support, while its da’wah strategy emphasizes dialogical, humanistic, and inclusive engagement rooted in universal Islamic values. As a result, ICC functions not only as a religious institution but also as a centre for social integration within London’s multicultural society, successfully promoting a moderate image of Islam and strengthening the religious identity of converts, thereby contributing significantly to the sustainability of Islam’s presence in Britain.